Throwing velocities, anthropometric characteristics, and efficacy indices of women's European Water Polo subchampions - Alcaraz, P. E.; Abraldes, J. A.; Ferragut, C.; Rodriguez, N.; Argudo, F. M.; Vila, H. (The Journal of Strength and Conditioning Research, 2011)
Water polo is a team sport characterized by a high-intensity, intermittent activity, where technical and tactical aspect are of a great importance. For that reason, the main aim of this study was to define the anthropometrical characteristics, maximum isometric grip strength, training and competition throwing velocities, and the efficacy indices in female high-level water polo players. A second purpose was to examine the differences between the throwing velocities in training vs. European championships in the water polo female national team. Ten elite trained female water polo players participated in this study. Before the competitive phase of their season, the following measures were taken: standard anthropometry, static and dynamic training throwing velocities, and hand-grip dynamometry. In the competitive phase, efficacy indices, average and maximum throwing velocities from all the participants were also determined. Significant differences (p <= 0.05) were found between different training situations and different competitive throwing velocities. We concluded that elite female water polo players modify their throwing velocity depending if the throw is performed during training or competitive situation.